2005
DOI: 10.4049/jimmunol.174.8.5057
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Deimination in Synovial Tissue Is Not Specific for Rheumatoid Arthritis but Commonly Occurs during Synovitides

Abstract: Autoantibodies to deiminated (citrullinated) proteins are the most specific serological markers of rheumatoid arthritis (RA). Deimination is critical in generating the peptidic epitopes they recognize. In the synovial tissue (ST), deiminated forms of the α- and β-chains of fibrin are their major autoantigenic targets (anti-human fibrin(ogen) autoantibodies (AhFibA)). We investigated whether the presence of deiminated fibrin in the ST was specific for RA, because this could explain why AhFibA are RA specific. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
88
0
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 62 publications
4
88
0
2
Order By: Relevance
“…These observations are consistent with findings of a recent study using different phage display antibodies and purified human ACPAs (49) as well as with our findings on deiminated fibrin using an antibody recognizing chemically modified citrulline epitopes independently of the amino acid context (20). The detection of different synovial deiminated proteins, some of which are RA specific, by distinct antibodies is not contradictory but rather indicates that not only citrulline, but also neighboring amino acids, determine the specific epitopes recognized by the different anticitrulline antibodies, mimicking the in vivo situation with ACPAs (16).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These observations are consistent with findings of a recent study using different phage display antibodies and purified human ACPAs (49) as well as with our findings on deiminated fibrin using an antibody recognizing chemically modified citrulline epitopes independently of the amino acid context (20). The detection of different synovial deiminated proteins, some of which are RA specific, by distinct antibodies is not contradictory but rather indicates that not only citrulline, but also neighboring amino acids, determine the specific epitopes recognized by the different anticitrulline antibodies, mimicking the in vivo situation with ACPAs (16).…”
Section: Discussionsupporting
confidence: 94%
“…The relevance of this finding is emphasized by several facts. First, previous studies failed to demonstrate a link between ACPAs and non-RA-specific citrullinated proteins, including fibrin (20,49). Second, our findings indicated that the presence of intracellular citrullinated proteins is independent of the degree of synovial inflammation and that the demonstrated link with ACPAs is thus not merely a secondary phenomenon due to higher ACPA levels leading to enhanced inflammation.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations